Manfaat E-Commerce terhadap Dunia Bisnis - Nurzanah, Siti; Riofita, Hendra (Ikatan Da'i Indonesia, 2024)
Electronic Commerce (e-commerce) is the process of buying, selling or exchanging products, services and information via computer networks. e-commerce is part of e-business, where the scope of e-business is broader, not only commercial but also includes business partners, customer service, job vacancies. Apart from www network technology, e-commerce technology also requires a database, email or electronic mail (e-mail), and non-computer technology as well as other delivery systems, and payment tools for e-commerce. With electronic commerce (e-commerce), customers can access and place orders from various places. Considering the increasingly advanced era of technology, customers who want to access e-commerce do not have to be everywhere, this is because in big cities in Indonesia there are many places that provide internet access facilities just by using a laptop/notebook. . or with a Personal Digital Assistant (PDA) using wifi technology. Thus, currently it is very necessary and desirable for companies to implement e-commerce services. The use of e-commerce in Indonesia is still very limited. From the existing background, the author will discuss how e-commerce is utilized for business purposes.